LION-PAW (lymphadenectomy in ovarian neoplasm) sexual function assessment: a prospective sub-study of the LION trial. Issue 10 (16th September 2020) - Hasenburg, Annette; Sehouli, Jalid; Lampe, Bjoern; Reuss, Alexander; Schmalfeld, Barbara; Belau, Antje Kristina; Bossart, Michaela; Mahner, Sven; Hillemanns, Peter; Petry, Ulrich; du Bois, Andreas; Herwig, Uwe; et al.
Abstract : Background: There is limited information about the impact of radical surgery including pelvic and para-aortic lymphadenectomy and subsequent platinum-based chemotherapy on sexuality in patients with advanced ovarian cancer. Objective: To evaluate the impact of radical surgery including pelvic and para-aortic lymphadenectomy and subsequent platinum-based chemotherapy on sexuality in patients with advanced ovarian cancer as a sub-protocol of the prospectively randomized LION trial. Methods: The Sexual Activity Questionnaire was applied to assess sexual function according to its sub-scales activity, pleasure, and discomfort. The 'orgasm' sub-scale from the Female Sexual Function Index was also added. The questionnaire was administered in combination with the EORTC QLQ-C30 questionnaire at baseline prior surgery, after 6, 12, and 24 months. The primary endpoint was changes in sexual function. Results: Overall, 495 patients received the questionnaires. 254 (51%) responded at baseline. Of these, 55 (22%) patients were sexually active, 182 (72%) were sexually inactive, and for 17 (7%) patients' data were not available. There was a total of 55/495 (11%) patients at 6 months, 139 (28%) patients at 12 months, and 81 (16%) patients at 24 months. Median age was 60.5 years (range 21.4–75.8). At baseline, sexually active responders were significantly younger (median age 51.5 years, ) than sexually inactive responders (median age 61.8 years) and tended to have a better performance status. Discomfort evaluated as dryness of the vagina and pain during sexual intercourse was significantly worse at 12 months than at baseline (p<0.001); however, the surgical variable, lymphadenectomy, did not have any impact on this. The orgasm sub-scale showed diverging results with a deterioration from baseline to 12 months in the lymphadenectomy group compared with the no-lymphadenectomy group (p=0.02). Conclusion: The majority of patients were sexually inactive; however, in those who were sexually active, pain during intercourse was worse at 12 months. In addition, the orgasm sub-scale demonstrated worse results in patients who underwent complete lymphadenectomy. The study suggests that surgery in the retroperitoneal space may influence sexual function.